Variasi Komponen Informasi Obat Pada Etiket Obat Resep - Isnenia, Isnenia; Satriawan, Ahmad Bayu (Jurnal Farmasi & Sains Indonesia, 2025)
Prescription drug label as a means of communication between pharmaceutical staff and patients.  Inadequate prescription drug labels can be a major source of medication errors. This can be exacerbated by the diversity of labels, formats, designs and information components. This study aims to observe prescription drug label in Bandar Lampung City health centers and to determine benefits of prescription drug label. This research was conducted cross-sectional on hypertensive patients regarding prescription drug label and its level of benefit. The results obtained show that there are two materials in prescription drug label. Every health center has a format for prescription drug labels. The label attached to the plastic clip does not contain the identity of the pharmaceutical service facility such as name, address and pharmacist's license. For printed paper labels, this information is a template that will be printed on all label materials that will be used. Information on the date and prescription number, patient name, instructions for use, and time to take the medication is available at all health centers. There is only one health center that has the format for address, date of birth, use, side effects, name of medicine and expiry date. More than 90% of respondents assessed that the labels provided were good and had a high level of benefit. The conclusion is that there are variations in the materials, formats and information components included in the dietetics. Medication labels are considered by patients to have a high level of benefit in the treatment process.